Antimicrobial susceptibility of Brucella melitensis in Kazakhstan - Ramankulov, Yerlan; Shevtsov, Alexandr; Syzdykov, Marat; Kuznetsov, Andrey; Shevtsova, Elena; Berdimuratova, Kalysh; Kasim, Mukanov (Nazarbayev University School of Sciences and Humanities, 2017)
Background: Kazakhstan belongs to countries with a high level of brucellosis among humans and farm animals. Although antibiotic therapy is the main way to treat acute brucellosis in humans there is still little information on a circulation of the antibiotic-resistant Brucella strains in the Central Eurasia. In this article we describe an occurrence of the drug resistance of Brucella melitensis isolates in Kazakhstan which is among the largest countries of the region. Methods: Susceptibilities to tetracyclin, gentamycin, doxycyclin, streptomycin and rifampicin were investigated in 329 clinical isolates of Brucella melitensis using E-test method. Results: All isolates were susceptible to streptomycin, tetracycline and doxycycline. 97.3% of the Brucella isolates were susceptible to gentamycin, although only 37.4% of isolates were susceptible to rifampicin. 21.9% of isolates had intermediate resistance, and 26.4% of isolates were resistant to this antibacterial drug. Conclusion: Isolates of Brucella melitensis circulating in Kazakhstan are susceptible to streptomycin, doxicyclin, tetracyclin and gentamycin. At the same time the resistance to rifampicin is widespread, almost half of the isolates were rifampicin-resistant (including the intermediate resistance).